Non-ergodic Processes in Athermal Martensitic Alloys Revealed by X-ray Photon Correlation Spectroscopy: Bulk Properties. (2015) - Widera, M.; Sprung, M.; Klemradt, U.
Abstract: The vast majority of martensitic transformations (MT) is classically viewed as being athermal, although time-dependent phenomena such as incubation time and/or aging effects have been known for a long time. Using highly coherent X-rays it has become possible to access non-equilibrium, intermediate states of the MT. X-ray photon correlation spectroscopy (XPCS) can reveal non-equilibrium dynamics using two-time correlation functions, where fluctuating intensities of X-ray speckle pattern are auto-correlated. Here we report XPCS experiments on a Ni63 Al37 alloy. The revealed isothermal dynamics shows non-equilibrium features on long time scales, superimposed with microstructural avalanches. The dynamics supports the "symmetry conforming short-range-order" model based on short range diffusion.